Functions and Regulation of Programmed Cell Death in Plant Development - Daneva, Anna; Gao, Zhen; Van Durme, Matthias; Nowack, Moritz K (Annual review of cell and developmental biology, 2016)
Programmed cell death (PCD) is a collective term for diverse processes causing an actively induced, tightly controlled cellular suicide. PCD has a multitude of functions in the development and health of multicellular organisms. In comparison to intensively studied forms of animal PCD such as apoptosis, our knowledge of the regulation of PCD in plants remains limited. Despite the importance of PCD in plant development and as a response to biotic and abiotic stresses, the complex molecular networks controlling different forms of plant PCD are only just beginning to emerge. With this review, we provide an update on the considerable progress that has been made over the last decade in our understanding of PCD as an inherent part of plant development. We highlight both functions of developmental PCD and central aspects of its molecular regulation.